The use of electronic resources among medical students in University of Hadramout - Balfaqih, Mohammed Abdulrahman (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2019)
The advent of modern ICT and technological revolution has brought about the rise of electronic resources in becoming an integral part of the modern education system, especially in tertiary education. The necessity for medical professionals to acquire high quality, authoritative, accurate, relevant and timely information, has permitted students studying in healthcare colleges to know the various electronic resources and the best appropriate way to access and use them. This study investigated the extent of use of electronic resources by undergraduate students of the College of Medical in Hadramout University (COMHU), their awareness and accessibility to electronic resources available in HUCOM library, as well as the problems being faced by them. The study employed survey method to collect the data which was done using questionnaire as the instrument for data collection. The study population comprised of 1513 students at the surveyed college, and a sample size of 306 students was used in the study. completed copies of the questionnaires were used for data analysis and were analyzed using (SPSS). The findings revealed that, though most of the students are aware and utilized the electronic resources offered by COMHU library, they could not access it easily and they need more orientation program whereby the COMHU library should put more effort in publicizing the electronic resources. It was further discovered that research purposes, complete course assignments and learning was among the main purposes of using the electronic resources. Some of the major problems indicated by the respondents using ERs includes poor internet connectivity; retrieving irrelevant information resources to meet their need; inadequate ICT infrastructure; interrupted power supply, etc. Recommendations are made in order to maximize the utilization of electronic information resources and address students' skills deficiencies which they experience while using ERs. The study concludes that the students in the college of Medical in Hadramout University need more orientation program, training in the use of electronic resources and need to gain more skills in searching techniques to have efficient and effective use of electronic resources.